Experimental and numerical study of diaphragm in-plane stiffness on the seismic performance of building structures with DCPCF - Yuan-yuan Sun; Rui Pang; Shu-ting Liang; Yi-ming Wen; Chun-lin Wang (Engineering Structures, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Genetic discrimination of the Dongshan Pb-Zn-Cu deposit based on sphalerite chemistry - Yi-Chen Chen; Shi-Jiong Han; Cheng-Gang Cao; Jun-Wei Bo; Yu-Rui Yuan; Ming-Yu Tang; Jin-Xin Yuan (Journal of Geochemical Exploration, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

The yield-biomass-water-environment nexus model unravels the plastic mulching film dilemma: Yield gains vs. environmental cascades in China’s cotton systems - Yifan Gu; Zixin Bian; Qianqian Shi; Ziyi Zhao; Haixia Li; Rui Li; He Peng; Ming Yang; Qingbin Yuan; Yufeng Wu (Agricultural Systems, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Mechanisms of Action of FUNDC1 in Cerebral Ischemia-Reperfusion Injury - Xin-Yi Zou; Luo-Yang Cai; Jin Zhang; Ying Yuan; Jie Song; Zhao-Duan Hu; Rui Peng; Xiao-Feng Ruan; Xiao-Ming Zhang (Molecular Neurobiology, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Dual-layer cellulose aerogel with integrated zirconium carbide-graphene oxide photothermal system for sustainable solar-driven seawater treatment - Ming Zhu; Siyue Yuan; Rui Zhang; Pengtao Liu (Carbohydrate Polymers, 2025)

Melichumarin A, a new coumarin with nitric oxide inhibitory activity from the stems of Melicope chunii - Rui-Hong Zhu; Zi-Feng Liang; Zhong-Liu Zhou; Zi-Ming Chen; Qi Zhou; Jing-Ling Ren; Shou-Yuan Wu (Natural Product Research, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Hierarchical bamboo-node architected cellulose nanofiber/polyvinyl alcohol aerogel embedded with nano-silicon carbide for enhanced solar thermal evaporation - Ming Zhu; Rui Zhang; Siyue Yuan; Pengtao Liu (Desalination, 2025)

Efficient synthesis of FePO4 from the incinerated sewage sludge ash by modification–selective leaching–precipitation - Zhong-hua Yang; Chuan-ming Du; Pei-yuan Ni; Lei Yuan; Yu-tang Zhang; Rui-yuan Yuan (Chemical Engineering Journal, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Synergistic reduction of pollutants and GHGs in China's PET industry: A material metabolism perspective - Fu Guo; Rui Li; Yifan Gu; Mingxuan Tuo; Zixin Bian; Yihan Li; Qingbin Yuan; Ming Yang; Yufeng Wu (Resources, Conservation and Recycling, 2025)

Advances in cellulose materials for interfacial water evaporation and their applications in seawater desalination - Ming Zhu; Rui Zhang; Siyue Yuan; Pengtao Liu (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Palynological assemblages from Hongguleleng Formation of Western Junggar, Northwest China and their correlation with conodont zonation - Zhen Shen; Philippe Steemans; Zélia Pereira; Rui-Wen Zong; Xin-Song Zhang; Kun-Yuan Ma; Yi-Ming Gong (Palaeoworld, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Effect of tunnel ventilation on surrounding rock temperature field and heat regulating circle during construction phase - Ming-Rui Luo; Yu-Chun Tao; Zuo-Bing Yuan; Liang-Liang Tao; Chuan He; Yan-Ping Yuan; Xiao- Yu Tian; Yan-Hua Zeng (Tunnelling and Underground Space Technology, 2024)

Optimal declutching control of hinged multiple floating bodies - Shuang-Rui Yu; Ming Zhang; De-Qing Zhang; Zhi-Ming Yuan (Ocean Engineering, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Attitude inversion of space debris based on the laboratory-tested photometry dataset - Shu-Shu Wang; Hou-Yuan Lin; An-Ming Kang; Jin-Rui Men; Chang-Yin Zhao (Advances in Space Research, 2024)

Model predictive control of wave energy converters - Ming Zhang; Shuang-Rui Yu; Guang-Wei Zhao; Sai-Shuai Dai; Fang He; Zhi-Ming Yuan (Ocean Engineering, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Phosphorus recovery from phosphate tailings through a two-stage leaching-precipitation process: Toward the harmless and reduction treatment of P-bearing wastes - Yao-hui Yu; Chuan-ming Du; Yu-tang Zhang; Rui-yuan Yuan (Environmental Research, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Polyrate 2023: A computer program for the calculation of chemical reaction rates for polyatomics. New version announcement - Rubén Meana-Pañeda; Jingjing Zheng; Junwei Lucas Bao; Shuxia Zhang; Benjamin J. Lynch; José C. Corchado; Yao-Yuan Chuang; Patton L. Fast; Wei-Ping Hu; Yi-Ping Liu; Gillian C. Lynch; Kiet A. Nguyen; et al. (Computer Physics Communications, 2024)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Time-optimal path planning and tracking based on nonlinear model predictive control and its application on automatic berthing - Ming Zhang; Shuang-Rui Yu; Kwang Sic Chung; Ming-Lu Chen; Zhi-Ming Yuan (Ocean Engineering, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Structural characteristics of the moss (bryophyte) layer and its underlying soil structure and water retention characteristics - Xia Hu; Zhou Gao; Xiao-Yan Li; Rui-Zhe Wang; Yuan-Ming Wang (Plant and Soil, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Study on the mechanical properties of coral sands with different particle gradations - Yuan-yi Chen; Yi Tang; Yun-fei Guan; Rui-ming Liu; Xun Han; Xian-qiang Zhao (Marine Georesources & Geotechnology, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Occurrence, correlation, and partitioning of organophosphate esters in soil and tree bark from a megacity, Western China - Can Wang; Rui-Yu Yuan; Shi-Qiang Wei; Ming-Jing He (Environmental Science and Pollution Research, 2023)

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Reduction the contamination of patulin during the brewing of apple cider and its characteristics - Zhouli Wang; Leran Wang; Qiaoying Ming; Tianli Yue; Qian Ge; Yahong Yuan; Zhenpeng Gao; Rui Cai (Food Additives & Contaminants: Part A, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Tamlana haliotis sp. nov., isolated from the gut of the abalone Haliotis rubra - Wen-Rui Cao; Bang-Tao Liu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Archives of Microbiology, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Comparison of different sampling strategies for debris flow susceptibility mapping: A case study using the centroids of the scarp area, flowing area and accumulation area of debris flow watersheds - Rui-yuan Gao; Chang-ming Wang; Zhu Liang (Journal of Mountain Science, 2021)

Ruegeria haliotis sp. nov., Isolated from the Gut of the Abalone Haliotis rubra - Wen-Rui Cao; Dan-Dan Shang; Bang-Tao Liu; Yi-Hao Hu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Current Microbiology, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Endothelial Progenitor Cells’ Classification and Application in Neurological Diseases - Jing-jing Yuan; Jing Yang; Shi-lei Sun; Rui Zhang; Yu-ming Xu (Tissue Engineering and Regenerative Medicine, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

IP-10/CXCR3 Axis Promotes the Proliferation of Vascular Smooth Muscle Cells through ERK1/2/CREB Signaling Pathway - Hui-jin Wang; Yu Zhou; Rui-ming Liu; Yuan-sen Qin; Ying-huan Cen; Ling-yu Hu; Shen-ming Wang; Zuo-jun Hu (Cell Biochemistry and Biophysics, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Systematic Review by Multivariate Meta-analyses on the Possible Role of Tumor Necrosis Factor-α Gene Polymorphisms in Association with Ischemic Stroke - Yu-Ming Niu; Hong Weng; Chao Zhang; Rui-Xia Yuan; Jin-Zhu Yan; Xiang-Yu Meng; Jie Luo (NeuroMolecular Medicine, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Preparation of malathion MIP-SPE and its application in environmental analysis - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Lei Shi; Ming Xing; Ping Guo; Yuan Ding; Hong Yang (Environmental Monitoring and Assessment, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)